Time-optimal control of a parabolic system with multiple time-varying lags - Kowalewski, Adam; Krakowiak, Anna (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the time-optimal control problem for a distributed parabolic system in which different multiple time-varying lags appear both in the state equation and in the boundary condition is presented. Some particular properties of the optimal control are discussed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka